Biological Fixed Film. (1st October 2015) - Kim, Eun‐Sik; Liu, Yang; Kim, Jeung‐Bea; Chang, Insoo; Choi, Jeongdong
Abstract : The review includes literatures published in the year of 2014 regarding the uses of biofilm and bioreactor to treat wastewater. Topics considered are: biofilm formation and factors that impact biofilm formation; extracellular polymeric substance from biofilms; biofilm consortia and quorum sensing; biofilm reactors and biofilm in bioelectrochemical systems.